PENGARUH PERSEPSI MANAJER TENTANG KEBIJAKAN PERUSAHAAN, PERILAKU KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS - Mudjiardjo Mudjiardjo (Universitas Negeri Jakarta, 2010)
The objective of this research is to find out the effect of manager’s perception to company policy, leadership behavior and work motivation on productivity. This research was conducted in Shipping Department of PT. Pertamina (Persero) Jakarta, on January to March 2008. The data were collected from 40 middle managers as unit analysis and selected by simple random sampling technique. The results of this research are as follow: (1). There is direct effect of the manager’s perception to company policy on work motivation, (2). There is no direct effect of manager’s perception to company policy on productivity, (3) There is direct effect of leadership behaviour on work motivation, (4) There is direct effect of leadhership behaviour on productivity, (5) There is direct effect of work motivation on productivity, (6) There is indirect effect of manager’s perception to company policy through work motivation on productivity, and (7) There is indirect effect of leadhership behaviour through work motivation on productivity. Therefore to increase productivity can be carried out by improving manager’s perception to company policy, improving leadhership behaviour and increasing work motivation.